(untitled) - Mascull, Bill (Harlow, 2005)
The new intermediate level also has a new video featuring seven films that relate to the langauge,skill and issues explored in the new course book. It is supported by a separate video resource book.
Keywords: English language,English language,Anh ngữ,Anh ngữ; Business english,Study and teaching,Tiếng Anh thương mại,Học và dạy